Diversity and functional capabilities of the microbial metagenome in a potable water reuse system - Arnold C.C. Wong; Elizabeth A. Dinsdale; Amanda Pham; Aleksey N. Pisarenko; Richard Gersberg; Matthew E. Verbyla (Desalination and Water Treatment)
The direct and indirect potable reuse of wastewater has recently gained significant attention in water scarce regions globally. Some advanced treatment facilities utilize ozone and biological activated carbon (BAC) filtration to remove persistent low molecular weight compounds, but the role of microorganisms in these systems has not been well studied. Previous studies of microbial communities in potable reuse systems have been limited to culture-based methods, targeted molecular methods, or 16S rRNA sequencing. The goal of this study was to use shotgun sequencing to characterize the phylogenetic and functional diversity at each point within a potable reuse treatment train in southern California, which consisted of primary clarification, activated sludge with nitrification and partial denitrification, tertiary filtration, ozonation, BAC filtration, membrane filtration, reverse osmosis, and UV/advanced oxidation. Samples were collected from the untreated wastewater and from the effluent of each treatment process. The data revealed significant shifts in phylogenetic and functional diversity at each point in the treatment train. The biofilm of the BAC filter was enriched with genes capable of degrading aromatic compounds, possessed mostly by Bradyrhizobia. The extracted final effluent sample only contained 0.3 ng/µL of microbial DNA—this was insufficient for shotgun sequencing, which requires at least 1 ng/µL.